Lived experiences of students in a public school enthusiast in playing mobile legends - Jericho D. Ecija; Reina Celine Sagales (Research Parks Publishing LLC, 2021)
The research study comprises a pure qualitative approach bounded in grounded theory and thematic analysis – a system of qualitative research that based on the data of the participants, the researcher will come up with the suggested principles on how to remediate the live experiences of the Mobile Legend Players who are also learners, and to give some collected data to be discussed as an authentic approach of comparing and relating the lived experiences of both study habits and the playing habits of the Grade 12 Learners of Salcedo Vocational High School